85.4k views
3 votes
Jorge says the first step to solving the equation below is to combine like terms on each side of the equal sign. David says you should distribute first then isolate x. Which perspective do you agree with and why? Determine the solution to the equation.

x + 2x + 3 + 3 = 3(x + 2)

1 Answer

4 votes

Answer:

1) David because of order of operations.

2) All Real Numbers

Explanation:

x + 2x + 3 + 3 = 3 (x + 2)

x + 2x + 3 + 3 = 3x + 6

3x - 3x = 6 - 6

0 = 0

User H B
by
5.9k points